Characteristics of LVB made of Gmelina Wood (Gmelina arborea Roxb.) with the Addition of Diammonium Phosphate and Sodium Silicate Fire Retardants - Eka Mulya Alamsyah; Aliesha Nur Azzahra; Yoyo Suhaya; Sutrisno Sutrisno; Ihak Sumardi; Atmawi Darwis; Asep Suheri; Jamaludin Malik; Sasa Sofyan Munawar (BioResources)
Laminated veneer board (LVB) panel from gmelina wood is one form of developing processed wood products to improve the quality of laminated veneer lumber (LVL). The addition of fire-retardant materials is an important element that needs to be developed to increase the fire resistance properties of LVL and LVB panels. The fire-retardant materials used in this research were diammonium phosphate (DAP) and sodium silicate (SS) with a concentration of 20% each, using two different application methods, namely impregnation and coating. This research aimed to determine the effect of adding 20% ​​DAP and 20% SS solutions on physical and mechanical characteristics, formaldehyde emissions, delamination percentage, and the burning time for LVB panels. Panel testing is carried out referring to the requirements of the ASTM D-143:2003 test standard for density, BS EN 317:1993 for swelling-shrinking, JIS A 1460 (2001) for formaldehyde emission, and JIS 701 (2008) for other parameters. Results from physical and mechanical tests showed that panels already met the standard. Formaldehyde emissions were less than 0.4.mg/L classified F**** which means the panel is safe and environmentally friendly. Percentages delamination already met the standard except for both SS impregnation and SS coating application methods. The longest burning time was achieved by the panel with added DAP impregnation.